Unraveling Motivational Beliefs in Learning English: Voices of Non-English Major Students in Indonesian Higher Education - Wahyuningsih, Sri; Erzad, Azizah Maulina (Journal of English Teaching and Learning Issues, 2023)
The present study attempts to explore the motivational beliefs in learning English among non-English major students from two higher educations in Indonesia. This study employed a qualitative descriptive approach. Data were collected through close-ended questionnaires. The questionnaires were then distributed to the 100 students. The collected data were then analyzed quantitatively to find out the percentage of motivational beliefs. Further, we interpreted the motivations mostly preferred the non-English major students. The results reveal that from 15 items of motivational beliefs in learning English, the most dominant motivations of learning English preferred by the non-English major students include becoming a knowledgeable person (95%), understanding English books, movies, music (95%), transferring knowledge to others (81%), becoming an educated person (81%), appreciating the ways of life of native English speakers (79%), discussing interesting topics in English with the people from other countries (77%), keeping in touch with foreign people (60%), getting appreciation from others (60 %). On the other hand, other items of motivational beliefs may not become their main motivational beliefs in learning English. This study presents an implication that students from non-English majors need to increase their self-awareness in learning English, particularly both in spoken and written ways to enhance their life.